Assessing the allocation of aid: developmental concerns and the self-interest of donors - Gustavo Canavire-Bacarreza; Peter Nunnenkamp; Rainer Thiele; Luis Trive\~no (The Indian economic journal, 2006)
In this paper, we perform a Tobit analysis of aid allocations, covering the period 1999-2002 and accounting for both altruistic and selfish donor motives. We first compare the allocative behavior of all bilateral donors taken together with that of multilateral aid agencies, and then look at nine major bilateral donors individually. It turns out that poorer countries get clearly more aid from both bilateral and multilateral donors, with the possible exception of France and Japan. Most bilateral donors and the multilateral agencies are also found to direct significantly more aid to well governed recipients if governance is measured by the World Bank?s CPIA. If the CPIA is replaced by the Kaufmann index, however, the policy orientation of aid becomes extremely weak. In contrast to a recent paper by Dollar and Levin (2004), our estimates do neither suggest that multilateral aid is more poverty and policy oriented than bilateral aid, nor that IDA performs particularly well within the group of multilateral donors. Post-conflict resolution, the third altruistic motive considered in the paper, emerges as a significant determinant of aid allocations in 2002. The importance of selfish aid motives clearly differs between bilateral and multilateral donors. We find no evidence that donor countries were able to push through their individual trade and political interests at the multilateral level. By contrast, the export-related self interest of DAC countries provided a fairly strong incentive to grant bilateral aid, as did colonial ties.
Keywords: F35; C24; 330; Foreign Aid Allocations; Donor Motives; Tobit Analysis; Entwicklungshilfe; Geberländer; Motivation; Internationale Wirtschaftsbeziehungen; Schätzung; Welt; Entwicklungsländer